Discrimination of two-point touch sense for the upper and lower extremity based on body mass index in young adults: an observational study - K. B., Riyas Basheer; Suresh, Anusree; P. R., Aiswarya; Rai, Subhashchandra (International Journal of Research in Medical Sciences, 2025)
Background: To establish normative values for two-point discrimination (TPD) across 11 dermatome regions in the upper and lower limbs while examining the correlation between TPD and body mass index (BMI) and the influence of gender-based variations on sensory perception. Methods: A cross-sectional observational study conducted with 200 healthy participants (100 males, 100 females) to measure TPD thresholds and analyse correlations with BMI. This study was carried out in a controlled clinical setting, ensuring minimal environmental interference in sensory assessment. Participants were tested in quiet, temperature-controlled conditions to maintain reliability. Normative values for TPD in upper and lower limb dermatome regions, Correlation between TPD and BMI assessed using Karl Pearson’s correlation test. Gender-based correlation differences evaluated using Karl Pearson’s correlation test. Results: A statistically significant positive correlation (p<0.05) was observed between TPD and BMI, indicating higher BMI is associated with increased TPD values across multiple dermatome regions. No significant differences (p>0.05) in TPD were found between males and females, suggesting BMI influences sensory perception similarly across genders. Regional variations in TPD were noted, emphasizing differences in tactile acuity across limb areas. Conclusions: This study successfully established reference values for TPD, providing critical insights into sensory perception variations based on BMI. The findings challenge previous assumptions by confirming BMI as a significant factor in tactile sensitivity. Standardized testing protocols are recommended for clinical applications and future research in neurophysiology and rehabilitation.